2018
DOI: 10.29252/beat-060207
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Appendicitis in Patients with a Normal White Blood Cell Count; A Cross-Sectional Study

Abstract: Objective: To investigate the clinical, imaging and laboratory findings for diagnosis of acute appendicitis (AA) in patients with a normal white blood cell count (WBCC). Methods: This retrospective cross-sectional study was conducted in Ankara Numune Training and Research Hospital, Ankara, Turkey, during a 1-year period. To determine diagnostic factors in AA in patients with normal WBCC, medical records of eligible patients were reviewed for demographic and clinical variables, as well as patient outcome. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…Suggestions were made that repeated TUS may show better diagnostic performance compared to the initial TUS as the progression of the inflammatory process in the appendix would make it easier to detect [ 4 ]. The role of observation and repeated laboratory and clinical examination is beyond the scope of this study, and should be studied in future, as currently used prognostic scores and laboratory tests can be misleading and have lower sensitivity and specificity than diagnostic imaging, especially in early disease [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suggestions were made that repeated TUS may show better diagnostic performance compared to the initial TUS as the progression of the inflammatory process in the appendix would make it easier to detect [ 4 ]. The role of observation and repeated laboratory and clinical examination is beyond the scope of this study, and should be studied in future, as currently used prognostic scores and laboratory tests can be misleading and have lower sensitivity and specificity than diagnostic imaging, especially in early disease [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging techniques and Alvarado scoring can support the clinical diagnosis of appendicitis and decrease the negative appendectomies. Elevated total leukocyte count (TLC) supports the diagnosis of AA but a normal TLC does not necessarily rule out acute appendicitis [ 7 ]. For the diagnosis of AA, TLC is neither sensitive nor specific.…”
Section: Introductionmentioning
confidence: 99%
“…But a recent meta-analysis has shown that combined diagnostic accuracy of laboratory findings and clinical findings is very high [ 11 ]. According to a study, negative appendectomy rate was 19% in patients while 80.9% of patients had acute appendicitis who presented with normal TLC with suspicion of Acute Appendicitis [ 7 ]. According to another study, in patients with normal TLC, 6% of patients had no inflammation per-operatively, 12% had minimal inflammation and 82% had moderate to severe inflammation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 More recent data suggest that an elevated WBC can reduce the need for preoperative imaging in the paediatric population, 8 while a normal preoperative WBC and C-reactive protein in the adult population may be independent markers for a negative appendix. 9,10 Indeed, while there is evidence to suggest that an isolated neutrophilia in the appropriate clinical context can support the diagnosis of AA, 10 WBC does not correlate with disease severity nor radiological findings. 11 Proposed guidelines from the Netherlands suggest the routine use of preoperative imaging for all patients with clinically apparent appendicitis.…”
Section: Introductionmentioning
confidence: 99%
“…A 2012 meta‐analysis and systematic review of more than 1000 patients demonstrated the poor predictive value of preoperative markers such as white blood cell count (WBC) and C‐reactive protein in suspected AA . More recent data suggest that an elevated WBC can reduce the need for preoperative imaging in the paediatric population, while a normal preoperative WBC and C‐reactive protein in the adult population may be independent markers for a negative appendix . Indeed, while there is evidence to suggest that an isolated neutrophilia in the appropriate clinical context can support the diagnosis of AA, WBC does not correlate with disease severity nor radiological findings…”
Section: Introductionmentioning
confidence: 99%